A study on the products of Local Collection Unit (LCU) of Standard Chartered Bank Ltd. - Tabassum, Tasnim (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.